The association between GERD symptoms severity and psychosocial health in palestine: a cross-sectional study - Qusay Abdoh; Fatima Masoud Al-Amouri; Mohammad Taleb Abed; Mohammed Motasem Jaber; Nour Mahmoud Yassin; Raheeq Mohannad shawahne; Hiba Sadder; Manal Badrasawi (BMC Research Notes)
Abstract Objective This study aimed to investigate the relationship between GERD and mental health status, alongside lifestyle factors and eating patterns among Palestinian adults. Results In this study, 144 participants with GERD were analyzed. GERD symptom severity was categorized into three groups: mild (35.4%), moderate (32.0%), and severe (32.6%), according to the GERD-HRQOL. Multiple linear regression analysis revealed that sleeping problems are the only predictor of GERD symptoms severity (B = 3.785, 95% confidence interval = 0.712–6.857, p = 0.016).